The Influence of Convenience and Quality of Information on Student Interest in Using M-Banking Services at Bank Syariah Indonesia - Mila Cahyawati; Resta Pratama Faudi; Bertha Salmania Putri; Hafifah Nur Hasanah; Agustina Dwi Utami; Izatil Khoiriyah (Proceeding International Conference Restructuring and Transforming Law, 2023)
"The Influence of Quality of Information on Student Interests in the Use of M-Banking" is the title of the article. Customers who serve as supporting facilities for the activities of all levels of society may be interested in technological advancements in this rapidly expanding era of globalization. One of the data advances in Islamic banking is the m-banking administration which is the improvement of two past types of development in Islamic banking, to be specific sms banking and web banking. It is hoped that the potential customer will decide to use m-banking services if they have shown interest. This indicates that a potential customer's interest is the most important factor in deciding whether or not to use information technology. The study's formulation of the issue:In order to effectively explain the claims made in the article's title and find reliable data, this qualitative study looked at relevant facts and theories.